CO2/HCO3− Accelerates Iron Reduction through Phenolic Compounds - Felix Müller (American Society for Microbiology, 2020)
ABSTRACT Iron is a vital mineral for almost all living organisms and has a pivotal role in central metabolism. Despite its great abundance on earth, the accessibility for microorganisms is often limited, because poorly soluble ferric iron (Fe3+) is the predominant oxidation state in an aerobic environment. Hence, the reduction of Fe3+ is of essential importance to meet the cellular demand of ferrous iron (Fe2+) but might become detrimental as excessive amounts of intracellular Fe2+ tend to undergo the cytotoxic Fenton reaction in the presence of hydrogen peroxide. We demonstrate that the complex formation rate of Fe3+ and phenolic compounds like protocatechuic acid was increased by 46% in the presence of HCO3− and thus accelerated the subsequent redox reaction, yielding reduced Fe2+. Consequently, elevated CO2/HCO3− levels increased the intracellular Fe2+ availability, which resulted in at least 50% higher biomass-specific fluorescence of a DtxR-based Corynebacterium glutamicum reporter strain, and stimulated growth. Since the increased Fe2+ availability was attributed to the interaction of HCO3− and chemical iron reduction, the abiotic effect postulated in this study is of general relevance in geochemical and biological environments. IMPORTANCE In an oxygenic environment, poorly soluble Fe3+ must be reduced to meet the cellular Fe2+ demand. This study demonstrates that elevated CO2/HCO3− levels accelerate chemical Fe3+ reduction through phenolic compounds, thus increasing intracellular Fe2+ availability. A number of biological environments are characterized by the presence of phenolic compounds and elevated HCO3− levels and include soil habitats and the human body. Fe2+ availability is of particular interest in the latter, as it controls the infectiousness of pathogens. Since the effect postulated here is abiotic, it generally affects the Fe2+ distribution in nature.